Inny i pedagogika: doświadczenie inności i relacja z Innym jako istotne kategorie nauk o wychowaniu - Rzeźnicka-Krupa, Jolanta (Wydawnictwo Naukowe UAM, 2013)
The text concentrates on the analysis of the relation between concepts and phenomena which can be perceived as different and other in social space and the area of educational studies. It attempts to research not only the theoretical roots but also seeks a kind of validation to undertake issues connecting with the “otherness” in the fi eld of pedagogical refl ection. The concept of category, understood as the way of organizing thinking around certain essential meanings and plots, makes it possible to link up the “Other“ and “relation with the Other” concepts with the problems which constitute the research area of contemporary pedagogy. It also makes possible to indicate some potential spheres of experiencing otherness and creating relation with the Other not only in the perspective of education but in the aspects of various practices constructing the social life and culture of community.
The Other and Pedagogy: the Experience of Otherness and the Relation with the Other as Crucial Categories of Educational Studies
Keywords: the other; relation with the other; category; educational studies